Analisis Komitmen Organisasi Pada Kantor Camat Asakota Kota Bima - Sri Endang; Ikbal Irawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Employees who have high organizational commitment will produce good performance, low absenteeism, lack of turnover, and employee discipline will increase when the employee commits to his work. Conversely, employees who have low organizational commitment will have a negative impact on the organization. This study aims to determine and analyze the amount of organizational commitment of employees at the Bima City Asakota District Office. This type of research is a descriptive study, with a sample of 46 respondents. The sampling technique used was purposive sampling. Data collection used observations, questionnaires, interviews and heritage studies. The method of data analysis used was the one-sample t-test and also using the SPSS program. The results of this study concluded that the Organizational Commitment at the Asakota District Office Kota Bima is more than 70% of the expected (high) as evidenced by the t test value of 13,670 and Sig 0,000. If compared between the value of t count with t table, the t count is greater than t table (13,670> 1,679), and the value of Sig <0.05 (0,000 <0.05) means that it is significant so that Ha is accepted and H0 is rejected